Proyek Gemilang: Pembentukan Karakter melalui Pendekatan Literasi, Sains, dan Keterampilan di SD Curahdami 3 - Azizah, Qurrotun; Zabita, Devara Fulavelya; Nandini, Salma; Saputra, Aris Yulio; Jazirah; Candra, Yoga Andika; Suud, Hasbi Mubarak; Puspito, Agung Nugroho (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The Gemilang Project aims to improve the competency of students at SDN Curahdami 3, Bondowoso, through project-based education that develops cognitive, emotional and physical aspects. Basic education plays an important role in forming quality individuals by emphasizing life skills and creativity. This project will be implemented over four weeks in the 2023/2024 academic year, involving practical activities such as planting chilies and creative activities such as drama and dance. The results show an increase in students' knowledge, skills and creativity. The use of innovative and traditional learning media has succeeded in increasing students' interest in learning. In conclusion, the project-based approach is effective in developing students' holistic potential. Thanks are expressed to all parties who contributed to the success of this project.